Media Coverage of Dilan’s Domestic Violence Case Involving Her Husband in Online Media: A Critical Discourse Analysis By Sara Mills - Nadiyatul Maghfiroh; Bambang Wibisono; Agus Sariono; Didik Suharijadi (Pusat Studi Gender Universitas Jember, 2026)
Domestic violence has become a significant social issue in Indonesia, and its representation in online media influences public perceptions of victims, perpetrators, and gender relations. This study aims to analyze the news coverage of Dilan’s domestic violence case published by Okezone.com by examining the representation of subject and object positions, as well as writer and reader positions, using Sara Mills’ Critical Discourse Analysis framework. A descriptive qualitative method was employed, with news texts published between 2024 and 2025 serving as the primary data. Data were collected through documentation and analyzed based on Sara Mills’ concepts of subject–object and writer–reader positions. The findings indicate that Dilan is predominantly positioned as the narrative subject because she is given extensive opportunities to express her experiences and emotions, while Safno is positioned as the object whose identity is constructed through the victim’s perspective. The writer reinforces the victim’s narrative through emotionally charged language, detailed descriptions, and visual evidence, thereby directing readers to sympathize with the victim and perceive the alleged perpetrator negatively. These findings demonstrate that Okezone’s news coverage is not neutral but constructs social reality by reproducing gendered representations and power relations through its discursive strategies.